Project Management Maturity Analysis in the Serbian Energy Sector - Marko M. Mihic; Dejan C. Petrovic; Vladimir Lj. Obradovic; Aleksandar M. Vuckovic (Energies, 2015)
In this paper we will present an analysis of the current state of practice in project management in the energy sector in Serbia, wherein the mentioned analysis is based on the results of original research on project maturity in this field. This paper includes a literature review about the current situation in the Serbian energy system, the basic concepts and significance of the research of project maturity in organizations, the basic concepts related to the projects in the energy sector, as well as the general state of project management in Serbia. After this, an analysis of the results of the research is presented, which is structured according to the elements of project maturity included in the research, and the methods of analysis. The analysis of the results includes a general analysis as well as statistical and cluster analysis. At the end, based on the analysis results, recommendations for improvements in the area of project management in the energy sector in Serbia are presented.